Hormonal contraceptive use and risk of HIV-1 disease progression - Heffron, Renee (2013)
BACKGROUND: For HIV-1 infected women, hormonal contraception prevents unintended pregnancy, excess maternal morbidity, and vertical HIV-1 transmission. Hormonal contraceptives are widely used but their effects on HIV-1 disease progression are unclear. METHODS: In a prospective study among 2269 chronically HIV-1 infected women from 7 countries in East and southern Africa and with enrollment CD4 counts ≥250 cells/mm(3), we compared rates of HIV-1 disease progression among those using and not using hormonal contraception (i.e. oral or injectable methods). The primary outcome was a composite endpoint of CD4 decline to <200 cells/mm(3), initiation of antiretroviral therapy, or death. RESULTS: 372 women experienced HIV-1 disease progression during 3242 years of follow up (incidence rate=11.5 events per 100 person-years). Rates of HIV-1 disease progression among women who were currently using and not using hormonal contraception were 8.54 and 12.31 per 100 person-years, respectively (adjusted hazard ratio [HR] 0.74, 95% CI 0.56–0.98, p=0.04). Rates were 8.58 and 8.39 per 100 person-years for the subsets using injectable and oral contraception (adjusted HR=0.72, p=0.04 for injectable users and adjusted HR=0.83, p=0.5 for oral users compared to women not using hormonal contraception). Sensitivity analyses assessing enrollment or cumulative contraceptive use during the study demonstrated risk estimates closer to 1.0 with no evidence for accelerated disease progression. CONCLUSIONS: Among African women with chronic HIV-1 infection, use of hormonal contraception was not associated with deleterious consequences for HIV-1 disease progression.